The quadratic formula is:
x = [ -b +/- sqrt(b² - 4ac) ] / 2a
So the two roots are:
[-b + sqrt(b² - 4ac) ] / 2a
[-b - sqrt(b² - 4ac) ] / 2a
To add these together, just add the numerators, since they have the same denominator.
[ -b + sqrt(b² - 4ac) + -b - sqrt(b² - 4ac) ] / 2a
Notice how the sqrt cancels out.
(-b + -b ) / 2a
= -2b / 2a
Then a 2 cancels out:
= -b / a
You can do a similar thing for the product.
For the two roots, multiply them together:
[-b + sqrt(b² - 4ac) ] / 2a * [-b - sqrt(b² - 4ac) ] / 2a
Remember to multiply two fractions, just multiply the numerator across, and also multiply the denominator across.
( [-b + sqrt(b² - 4ac) ] * [-b - sqrt(b² - 4ac) ] / ( 2a * 2a )
Whenever you have (X + Y)(X - Y), remember that outer and inner terms (XY and -XY) cancel out. Thus it is just X² - Y²
So this simplifies to:
[ (-b)² - (sqrt(b² - 4ac))² ] / 4a²
This further simplifies to:
[ b² - (b² - 4ac) ] / 4a²
Then the b² cancels out:
4ac / 4a²
Now cancel 4a from top and bottom:
c / a
So the sum of the roots is -b / a
And the product of the roots is c / a
2006-10-17 13:24:41
·
answer #1
·
answered by Puzzling 7
·
0⤊
0⤋
The answer lies in the general solution to a quadratic equation, which is usually just termed "the quadratic equation." This gives the general solution to the quadratic equation:
a * x^2 + b * x + c = 0
as: x1 = (-b + sqrt(b^2 - 4*a*c))/2a and x2 = (-b - sqrt(b^2 - 4*a*c))/2a
Do the algebra and you will see that x1 + x2 = -b/a and x1*x2 = c/a
2006-10-17 20:32:33
·
answer #2
·
answered by Pretzels 5
·
0⤊
0⤋
Well, the quadratic formula (general solution for a quadratic equation) is
[-b +- sqrt(b^2 - 4ac)]/2a
giving two roots - adding them together = -2b/2a = -b/a
Multiplying them together = (b^2 - b^2 + 4ac)/4a^2 = c/a
2006-10-17 20:31:28
·
answer #3
·
answered by kindricko 7
·
0⤊
0⤋
This falls out of the usual formula for solving a quadratic equation. It is fairly easy to derive (and thus prove) this formula.
2006-10-17 20:20:49
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
This comes from the quadratic formula:
x1=(-b+â(b²-4ac))/(2a), x2=(-b-â(b²-4ac))/(2a)
x1+x2 = (-b - b + â(b²-4ac) - â(b²-4ac))/(2a) = -2b/(2a) = -b/a
x1*x2 = (b² + bâ(b²-4ac) - bâ(b²-4ac) - (b²-4ac))/(4a²) = (b²-b² + 4ac)/(4a²) = 4ac/(4a²) = c/a
The quadratic formula itself may be proven from the process of completing the sqauare:
ax² + bx + c = 0
x² + bx/a + c/a = 0
x² + bx/a = -c/a
x² + bx/a + (b/(2a))² = -c/a + (b/(2a))²
(x + b/(2a))² = -c/a + (b/(2a))²
(x + b/(2a))² = -c/a + b²/(4a²)
(x + b/(2a))² = -4ac/(4a²) + b²/(4a²)
(x + b/(2a))² = (b²-4ac)/(4a²)
x + b/(2a) = ±â(b²-4ac)/(2a)
x=(-b±â(b²-4ac))/(2a)
2006-10-17 20:23:41
·
answer #5
·
answered by Pascal 7
·
0⤊
0⤋
http://www.phar.cam.ac.uk/docs/emb/sbh_quad.pdf might help.
2006-10-17 20:23:59
·
answer #6
·
answered by maegical 4
·
0⤊
0⤋